Presença na contística de João Anzanello Carrascoza: o enlace amoroso entre a prosa e a poesia - Boainain, Regiane Magalhães (2024)
This thesis focuses on analyzing the presence in João Anzanello Carrascoza's short stories, highlighting the unique ability of this language to impact the reader. The research begins by questioning whether presence, understood as the transition from the virtuality of the page to a tangible experience for the reader, is evidence of the poetic in Carrascoza's tales. The central hypothesis contends that language devices in the author's work produce this presence, allowing the reader to vividly experience it. Therefore, the aim of this research is to assess whether there is a presence in the author's short stories and, if so, by what language devices it is produced. The identified language procedures responsible for the production of presence include contemplative description, metaphor, focalization management, the choice of narrative plans close to the object, the preference for the present as a narrative time, brevity, and phrasal cuts. With these elements, the lyrical prevails in a prose that increasingly leans towards poetry. Given the vastness of Carrascoza's work, the thesis focuses on the short story genre and adopts a temporal division, categorizing his short stories into two phases: from 1994 to 2004 and from 2010 to 2020, using O volume do silêncio (2006) as a dividing point. This division aims to investigate whether there is a presence in specific moments and, if so, identify the types of presence before and after 2006. As a result, the analysis revealed two distinct types of presence: the unveiling of Being, present throughout the author's career, and the unveiling of language, emerging in the second phase, especially in works like Linha única, characterized by the poetics of brevity, and Conto para uma só voz, marked by the poetics of phrasal cuts. To achieve the goal and navigate the path that leads to the observation of presence in the short stories, the thesis is organized into three chapters: The first delves into Hans Ulrich Gumbrecht's theory of presence, highlighting its conception as an experience that transcends mere sense apprehension. The second chapter explores the relationship between presence and language, proposing a rearrangement of the model proposed by Gumbrecht. The third chapter describes the types of presence observed in the selected corpus: O volume do silêncio, Linha única, and Conto para uma só voz. The research contributes to literary studies by expanding the critical fortune of the author, exploring presence in his work in an unprecedented way. Additionally, it offers an analysis of fictional procedures that generate the poetic effect in Carrascoza's short stories, filling a gap in existing research. The thesis also suggests possible directions for future research, including the analysis of presence in other literary genres and the investigation of the effects of presence in novels and children's and young adult literature